Systematic Characterization of In Vitro and In Vivo Metabolic Pathways and Identification of Novel Biomarkers of 26 Synthetic Cannabinoids - Yudie Ning; Tao Wang; Xiao Yang; Fang Guo; Yingwen Xu; Yuan Zhang; Kaile Wang; Meng Hu; Zhe Chen; Zhiwen Wei; Keming Yun (Molecules, 2025)
In recent years, the harms and abuse of synthetic cannabinoids (SCs) have attracted extensive attention in society. Their structures have been updated rapidly, which brings great challenges for continuous detection and drug identification. The aim of this study was to elucidate the metabolites of 26 kinds of abused SCs produced in human liver microsomes (HLMs) and rats and to explore the metabolism of indole amides, indazole amides, azaindoles, naphthyl indoles, cyclopropylindoles, naphthyl benzimidazole, and naphthyl pyrrole SCs in vivo and in vitro. Human liver microsomes were incubated with SCs to simulate human metabolic processes, and the in vitro metabolic model of liver microsomes was established. After the SD rats were randomized into groups, 26 kinds of SCs and normal saline were injected respectively to establish the rat model after exposure. The metabolites were identified one by one using a UHPLC-Q-Exactive Orbitrap MS method to explore the metabolic law. A total of 609 metabolites were identified, involving 30 metabolic pathways. The metabolism of SCs was summarized from the parent nuclear group, the head group, the linking group, and the tail side chain, and the mass spectral fragmentation pattern of the metabolites was analyzed in order to provide reference for the examination and identification of SCs-related cases.